Usability in the opening of soft drinks packagings: Age influence in biomechanical forces - Silva, Danilo Corrêa [UNESP]; Paschoarelli, Luis Carlos [UNESP] (My University, 2012)
Packagings have gone through profound changes. New materials and processes allow different designs, which became true consumer appeals. However, these advances do not necessarily lead to improvement in the usability of such products. This paper assesses how the different shapes of soft drinks PET bottles affect the ability of different age groups to open them. The results show that the adults have a greater strength in all situations when compared to youth or elderly subjects. A comparison of collected data and the torque forces necessary to perform the opening reveals a lack of usability and accessibility of these products.